A calcium-mobilizing biostimulant provides tipburn control comparable to vertical airflow fans in greenhouse hydroponic lettuce ‘Rex’ - Moosavi-Nezhad, Moein; Meng, Qingwu (Frontiers in Plant Science, 2025)
Lettuce (Lactuca sativa) tipburn is a calcium-related physiological disorder affecting young, enclosed leaves, reducing marketability. Vertical airflow fans (VAFs) effectively control tipburn in greenhouses but are limited by installation complexity, shading, and energy use. A chemical biostimulant can be added to hydroponic nutrient solution to enhance calcium mobility and reduce tipburn, but its efficacy relative to VAFs is unknown. We evaluated three biostimulant concentrations (0, 0.25, and 0.5 mL·L−1) with and without VAFs (≈1 m·s−1) in a split-plot randomized complete block design using greenhouse deep-water-culture hydroponics in summer. Lettuce ‘Rex’ plants were assessed 14, 21, and 28 days after transplant (DAT). Tipburn severity rating (on a scale from 0 = none to 5 = severe) and the percentage of leaves affected increased over time in the control (NoVAFs, no biostimulant), reaching 5.0 and 39%, respectively, at 28 DAT. Application of the calcium-mobilizing biostimulant at 0.5 mL·L−1 reduced tipburn by 94%–96% and 71%–75% at 21 and 28 DAT, respectively, under NoVAFs, comparable to the elimination or minimization of tipburn by VAFs. Shoot fresh and dry mass were transiently reduced by 16%–32% at 14–21 DAT under the highest biostimulant concentration, but by 28 DAT, biomass was comparable to the control across treatments, and minor reductions in tissue moisture content under VAFs explained fresh-mass differences. Inner-leaf calcium concentrations increased with biostimulant application under NoVAFs, correlating inversely with tipburn severity, whereas VAFs promoted calcium delivery independently of the biostimulant. These results demonstrate that the calcium‐mobilizing chemical biostimulant results in comparable tipburn mitigation in hydroponic lettuce to VAFs under summer greenhouse conditions, with no yield penalty at final harvest, and can be used where VAFs are impractical.